Characteristics of the blood–brain barrier in pediatric brain tumors - Gao, Qiang; Song, Dengpan; Xu, Dingkang; Chai, Xinyi; Ge, Ming (Frontiers in Pediatrics, 2025)
The blood–brain barrier (BBB) plays a vital role in maintaining central nervous system homeostasis but poses a major obstacle to effective drug delivery in pediatric brain tumors. BBB integrity varies significantly in pediatric brain tumors compared to adult ones, and is influenced by the tumor type, molecular subtype, and anatomical location. This review discusses the heterogeneous nature of the BBB across various pediatric brain tumors, including low-grade gliomas, diffuse midline gliomas, medulloblastomas, ependymomas and craniopharyngiomas. We review histological, molecular, and imaging evidence to highlight differences in BBB permeability and their implications for therapeutic delivery and treatment resistance. Special consideration is given to advanced drug delivery strategies, such as focused ultrasound and BBB-disrupting agents, which have been tailored to the unique barrier properties of each tumor subtype. A deeper understanding of tumor-specific BBB architecture is essential for tailoring treatment strategies and improving outcomes in pediatric brain cancer.